ANALYSIS OF FACTORS AFFECTING PURCHASE DECISION AT GRAMEDIA BOOKSTORE SEMARANG - Satya, Ardhian Prima; Nugraha, Hari Susanta; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2012)
There are many factors affecting consumer before they decide to purchase something at store. The factors are coming from outside dan inside of consumer which are common known as external factors and internal factors. There are kind of external factors such as location, product, price, service quality and promotion come from the store or seller. The Top Brand Award achievement to Gramedia Bookstore on last three years are showing that Gramedia Bookstore is the top of mind bookstore in Indonesia. This achievement be a self motivation to Gramedia Bookstrore to keep it from the competitors, including at Semarang. The purpose of this study is to determine the factors affecting purchase decision of Gramedia Bookstore consumer in Semarang. Type of this research is explanatory research. The sample of this research are 150 people. The sampling technique is using a purposesive sampling. The data were collected by using the questioner which are spread to three Gramedia Bookstore in Semarang. There were 50 poeple every bookstore. The data obtained were analyzed using analytical tools such as simple linear regression, linear regression testing and statistical test using t test and F test by using the SPSS 19 program. The research conclusions obtained indicated that factors such as location, product, price, service quality, promotion are simultaneously significant affecting the purchase decision of consumer at Gramedia Pandanaran and Pemuda. But aren’t simultaneously significant at Gramedia Java Supermall. The most dominant factors affecting purchase decision at Gramedia Pandanaran and Java Supermall is service quality. At Gramedia Pemuda, product is the most dominant factors affecting purchase desicion.